Disseminated Gastric MALT Lymphoma with Monoclonal Gammopathy, t(11;18)(q21;q21), and Subsequent Development of T-Large Granular Lymphocytic Leukemia: A Case Report and Review of the Literature - Riad Akoum; Wassim Serhal; Hussein Farhat (Case Reports in Medicine)
Background. Extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT) is a well-characterized entity that may share clinical and morphological findings with other low-grade non-Hodgkin’s lymphomas. Dissemination of MALT-type lymphoma to bone marrow and peripheral blood simultaneously with the presence of T-large granular cell leukemia (T-LGL) has rarely been reported. Case Presentation. This is the case of a 42-year-old male who presented with a gastric MALT-type lymphoma, disseminated to the bone marrow and the peripheral blood with high serum IgM levels and t(11;18)(q21;q21). The morphological, immunophenotypical and, immunohistochemical studies of the successive bone marrow and peripheral blood samples had revealed the coexistence of two distinct lymphoma cell populations: a B-cell, marginal zone type population expressing CD19, CD20, CD22, CD79b, IgM, and kappa light chain, and a T-large granular cell population, developed after treatment with rituximab expressing CD3, CD8, CD5, CD7, and CD45. Conclusion. Based on the analysis of this unusual case we performed an extensive review of the literature to elucidate the relationship between T-LGL and B-cell lymphomas and to emphasize the importance of paraprotein analysis at diagnosis of gastric MALT lymphoma.